2014
DOI: 10.1038/ajgsup.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Opioids and their Effects on Gastrointestinal Function

Abstract: Opioids are perhaps the most effi cacious analgesic agents available to the clinician in everyday clinical practice. While providing highly effective pain relief, the therapeutic activity of opioids is compromised by gastrointestinal adverse events related to their interaction with the opioid signaling system of the gut, a complex network of peptides and receptors with opioid-like properties that helps to coordinate gastrointestinal motility and secretion. The effects of opioids on the gut are modulated by gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 76 publications
0
38
0
Order By: Relevance
“…Opioid receptors are also extensively present in the gastrointestinal tract within enteric nerve plexuses and play a physiological role in gut muscle activity and control of fluid and electrolyte absorption. Inhibition of these receptors by exogenous opioids reduces gut motility and propulsive contractions, while also decreasing absorption of fluid and electrolytes from the gastrointestinal tract . Opioid induced inhibition of gastrointestinal motility is clearly a very important consideration in planning analgesia within an enhanced recovery program.…”
Section: Opioidsmentioning
confidence: 99%
“…Opioid receptors are also extensively present in the gastrointestinal tract within enteric nerve plexuses and play a physiological role in gut muscle activity and control of fluid and electrolyte absorption. Inhibition of these receptors by exogenous opioids reduces gut motility and propulsive contractions, while also decreasing absorption of fluid and electrolytes from the gastrointestinal tract . Opioid induced inhibition of gastrointestinal motility is clearly a very important consideration in planning analgesia within an enhanced recovery program.…”
Section: Opioidsmentioning
confidence: 99%
“…Historically, it has been indicated that opium was used in the Middle East as early as 4,000 BC. Later, the Greeks and Romans fully aware of the analgesic and euphoric properties of opium used as a drug for pain relief and recreation [2]. It has been found that half of the world's opioid users (7.8 million) are Asian with the highest prevalence rates reported from Iran, Kyrgyzstan and Laos [3].…”
Section: Introductionmentioning
confidence: 99%
“…OIC occurs because opiate-based pain treatment targets primarily one of three selective G protein-coupled opioid receptors (m, k, and d), namely the m-opioid receptor, expressed in the enteric nervous system of the digestive tract [12,17,[22][23][24][25][26][27][28]. Initial management and prevention of OIC, include the use of stool softeners, osmotic agents, and stimulant laxatives, however, their efficacy in advanced illness and chronic noncancer pain patients is limited and targeted pharmacological therapy is often needed, [14,20,[29][30][31][32] including prokinetic agents and peripheral m-opioid receptor antagonists [12,17,22,24,25,[32][33][34]35 && ].…”
Section: Introductionmentioning
confidence: 99%